Avaliação do mapa sonoro de tráfego veicular no município de Natal/RN - Florêncio, Débora Nogueira Pinto (2018)
Sound pollution is already considered by the World Health Organization (WHO) the second largest cause of global pollution. In a general context, urban development was accompanied by the accelerated growth of cities and the increased circulation of motor vehicles, causing higher levels of noise pollution. Urban environments present complex acoustic scenarios and studies about them need to consider the impact of several sound sources. Computational models become facilitators, evaluating possible solutions, since they enable fast calculations, analyzes and reports. With this feature, it is possible to know the sound pressure levels at any point in a modeled area, through direct reading on the sound map. The research problem appointed in this dissertation is: How traffic noise can be spatialized in Natal street system? The hypothesis points to sound pressure levels above those recommended by legislation in arterial and "secondary" streets of Natal/RN. Therefore, this research aims to evaluate the quality of the sound environment and its relation with the road network in Natal / RN, by mapping traffic noise with a computational model assistance. We gather and analyze traffic data, acoustic and physical-environmental conditioning maps as methodological procedures. Then, sound maps were processed through computer simulation software. These maps were calibrated based on quantitative acoustic measurement data on site. As results, it was verified that the vehicular flow follows a pattern of growth based on variables such as width and length of the track. There is a strong correlation between vehicle flow and sound pressure levels. The average equivalent level of noise (LAeq, 7-22h) in t Natal is 75.4% higher than the 55dB recommended by NBR 10151 (ABNT, 2000) for residential use and excess 15.3% on the 65dB World Health Organization recommendation (WHO, 1999). In the marginal street range (from curb to 100m) 95.8% extrapolate the 65dB in arterial pathways. Finally, from the diagnosis of the attributes involved, the guidelines for planning in the environmental acoustics were elaborated, in order to minimize the noise impact.